Effect of hydrated C60 fullerene on lipid, vitamin and amino acid composition in frozen-thawed ram semen - Turk, Gaffari; Koca, Recep H.; Gungor, Ibrahim H.; Cinkara, Serap Dayan; Acisu, Tutku C.; Erisir, Figen Erdem; Karatepe, Mustafa (Elsevier, 2022)
This study was conducted to investigate the effect of different doses of hydrated C-60 fullerene (C(60)HyFn) on freeze-thawing process-induced changes in lipid, vitamin and amino acid composition and also in motility, kinematic, sperm quality and oxidative stress parameters in ram semen. Semen was collected from seven rams twice a week for 3 weeks, so six repetitions were performed. The semen collected in each repetition was pooled. Each pooled sample was diluted with tris + egg yolk extender with (200 nM, 400 nM, 800 nM, 1 mu M and 5 mu M) and without (control) C(60)HyFn and they were frozen in mini straws. The doses of 800 nM, 1 mu M and 5 mu M had higher total, progressive motility, sperm membrane functionality rates, glutathione-peroxidase and catalase activities. All doses of C(60)HyFn significantly reduced dead and total abnormal sperm rates and malondialdehyde levels. Significant increases in vitamin A (400 and 800 nM doses), vitamin K1 (400 nM, 800 nM and 1 mu M doses), total amino acid (all doses) levels, but significant decreases in vitamin D2 (800 nM, 1 and 5 mu M doses), vitamin D3 (1 and 5 mu M doses) and vitamin E (200 nM, 1 and 5 mu M) levels were observed compared to control. In conclusion, the addition of C(60)HyFn to ram semen at 200 nM -5 mu M range, especially at a dose of 800 nM, provides a positive contribution to the protection of motility, vitamins A, K and total amino acid levels, and oxidant/antioxidant balance after freeze-thawing.
Keywords: Amino acid; Fatty acid; Freeze-thawing; Hydrated carbon 60 fullerene; Ram semen; Vitamin